1999
DOI: 10.1159/000014153
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Antigenic Concentrations of Alpha-1-Proteinase Inhibitor after Administration for the Prevention of Chronic Lung Disease of Prematurity

Abstract: Objective and Methods: Alpha-1-proteinase inhibitor (A1PI) supplementation has been used in adults with inherited alpha-1-antitrypsin (A1AT) deficiency to impede the development of emphysema. A1PI supplementation may also be useful for protecting premature neonates who receive mechanical ventilation from the development of chronic lung disease (CLD). However, the pharmacokinetics of exogenous A1PI in this population are unknown. We attempted to determine the disposition of A1PI in premature infants with birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Consistent with the above observations, a randomized clinical trial of ␣ 1 -AT supplementation reduced the incidence of pulmonary hemorrhage but did not affect the incidence of BPD in premature infants with respiratory distress syndrome who had also received surfactant treatment (46). In this trial, the plasma concentrations of ␣ 1 -AT were not significantly different between the placebo and control groups (47) and thus could account for the ineffectiveness of ␣ 1 -AT. Our study as well as the previously published studies (42,49) suggest that low levels of NE in new BPD may have contributed to the lack of a statistically significant clinical benefit from ␣ 1 -AT supplementation.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with the above observations, a randomized clinical trial of ␣ 1 -AT supplementation reduced the incidence of pulmonary hemorrhage but did not affect the incidence of BPD in premature infants with respiratory distress syndrome who had also received surfactant treatment (46). In this trial, the plasma concentrations of ␣ 1 -AT were not significantly different between the placebo and control groups (47) and thus could account for the ineffectiveness of ␣ 1 -AT. Our study as well as the previously published studies (42,49) suggest that low levels of NE in new BPD may have contributed to the lack of a statistically significant clinical benefit from ␣ 1 -AT supplementation.…”
Section: Discussionsupporting
confidence: 78%
“…superoxide dismutase [26,27], protease inhibitors, i.e. alpha-1-proteinase [28,29], as well as current investigation of agents with anti-inflammatory potential, i.e. recombinant human Clara cell 10 kD [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of patients was small, no statistically significant difference in the incidence of BPD was found between the treated and the placebo group. A subsequent report suggests that a high plasma clearance of α1P1 in the neonate may result in inadequate plasma concentrations [116]. In addition, long-term follow-up studies have not been reported, and thus it is not known whether a "delayed" benefit might have been observed.…”
Section: Antiproteinasesmentioning
confidence: 99%